British Thoracic Society guidelines for the management of spontaneous pneumothorax: do we comply with them and do they work?. Issue 5 (September 1998) - Soulsby, T
Abstract : OBJECTIVES: To determine how British Thoracic Society (BTS) guidelines for the management of spontaneous pneumothorax have been implemented over a four year period in a large district general hospital with a specialised respiratory unit. To assess the validity of the guidelines in the management of spontaneous pneumothorax. METHODS: A retrospective case notes study over a four year period for all patients with spontaneous pneumothoraces attending the accident and emergency (A&E) department of a large district general hospital. RESULTS: 115 episodes of spontaneous pneumothorax were identified. Overall 20.8% of episodes were treated correctly by BTS guidelines. Decisions made by A&E staff were significantly more likely to be correct than decisions made by on call medical teams (39.4% v 13.4%, p = 0.002). There was a non-significant trend towards better compliance with BTS guidelines over the four year period. The management decision was made by A&E staff only in 28.7% of episodes. Patients without chronic lung disease could be safely observed as outpatients. Forty three pneumothoraces were aspirated: 23 (58%) successfully; eight (18.6%) with little or no improvement; and 12 (27.9%) initially successfully but developing increased size of pneumothorax within a period of 72 hours. Three patients had repeat aspirations, two successfully. Age over 50, chronic lung disease, and more than 2.5 litres of air aspirated were significantly associated with failure of aspiration (p < 0.01). There was a 28.6% failure rate of aspiration for patients with moderate pneumothoraces without chronic lung disease. CONCLUSIONS: Patients over the age of 50 should be treated the same as patients with chronic lung disease. A second aspiration should be attempted if the first aspiration is initially successful with subsequent recurrence of pneumothorax. Further research is required to clarify if patients with moderate pneumothoraces under the age of 50 and no chronic lung disease should be aspirated or observed.